(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Over the past years, protection of the rights of the vulnerable such as women with special needs has been the concern of most international human rights treaties and institutions. In 2008, the UN adopted the Convention on the Rights of Persons with Disability; mandating state parties to take positive measures to ensure proper and effective protection of the rights of the PWSNs including women. Cameroon being a party to this treaty hided to the call of the UN put in place legal, institutional and policy measures for effective enforcement of the rights of these persons. Despite the measures taken by the state of Cameroon, it is found that women with special needs still experience violation of their rights due to the fact that the stakeholders charged with the responsibility to protect WWSNs are faced with various challenges which hinder effect enforcement and implementation of the laws.